If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-5 + 6x) = -15 (-5 * 3 + 6x * 3) = -15 (-15 + 18x) = -15 Add '15' to each side of the equation. -15 + 15 + 18x = -15 + 15 Combine like terms: -15 + 15 = 0 0 + 18x = -15 + 15 18x = -15 + 15 Combine like terms: -15 + 15 = 0 18x = 0 Solving 18x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '18'. x = 0 Simplifying x = 0
| -17-9y=0 | | 6(-6-2x)=96 | | -5(7x+7)=-175 | | 5(2+3x)=-140 | | 3+1=n+3 | | 3(1x+4)=6 | | 4(7x+1)=200 | | -14-12x+30=28 | | 2m-3(5m-7)= | | 2(5x-2)=56 | | 3A-c+2a-3c= | | 7h-15=55 | | y^2+3y-7=6y+3 | | 3p+8-3(p+4)=1 | | 45.00(15+x)=1935.00 | | f(b)= | | 8x-x=10+1 | | 3x-2(4)= | | f(x)=x^3+4x^2+9x+10 | | 9x=5(2x-1) | | Y=3.5x+1 | | 8x+1=10-x | | 4x+5xy=18 | | x^2+2z-35=0 | | 1-x=3x+29 | | y^2-3y-14=0 | | 7x^3-50x=0 | | a+3b=5 | | 11-24= | | x-.30x=91 | | x^2-25x-440=0 | | 15x-10+21x+7=-9+3x+16+x |